A highly reactive and magnetic recyclable catalytic system based on AuPt nanoalloys supported on ellipsoidal Fe@SiO21. Issue 8 (28th February 2015) - Zhang, Zewu; Zhou, Yuming; Zhang, Yiwei; Zhou, Shijian; Xiang, Sanming; Sheng, Xiaoli; Jiang, Ping
<x xml:space="preserve">Abstract</x> A facile method based on in situ reduction is described for constructing AuPt nanoalloys on Fe@SiO2 with high catalytic activity and convenient magnetic separability.